Heat exposure and self-rated health in older Chinese adults: the mediating roles of chronic disease and intergenerational support, 2008–2018 CLHLS - Wang, Huan; Wang, Danyang (Frontiers in Public Health, 2025)
BackgroundUnder the dual pressures of global warming and accelerated population aging, rising temperatures pose a particularly serious threat to the older population. However, systematic evidence on the heat exposure-response pathway is still scarce. This study aims to explore the effects of heat exposure on self-rated health and its pathways in older adults in China. We predicted that heat exposure would reduce the self-rated health of older adults, and that chronic diseases and intergenerational support would mediate this effect.MethodsWe linked health data from 9,670 participants in the Chinese Longitudinal Healthy Longevity Survey (CLHLS, 2008–2018 waves) with meteorological records from the National Climatic Data Center (NCDC). Individual fixed-effects models were employed to disentangle acute versus cumulative thermal effects, while Bootstrap-mediated path analysis quantified the mediating mechanisms involving chronic disease proliferation and deterioration of intergenerational support.ResultsHeat exposure has a time effect on the health risk of older adults, and long-term heat exposure (β = −0.156, p < 0.01; β = −0.003, p < 0.01) significantly reduces self-rated health through the cumulative effect of health disadvantages than short-term exposure (β = 0.004, p < 0.1; β = −0.001, p > 0.1). The increase in the number of chronic diseases (β = 0.260, p < 0.05) and the weakening of children’s intergenerational support (β = −0.052, p < 0.01; β = −0.023, p < 0.01) constitute a mediating pathway at individual and household level separately.ConclusionWe found that chronic diseases and intergenerational support from children mediated the effect of heat exposure on the deterioration of self-rated health in older adults. Empirical evidence substantiates the necessity for a tiered intervention framework encompassing: individual-level chronic disease co-management protocols; household-driven initiatives to reinforce intergenerational support. This stratified approach alleviates bioclimatic risks through coordinated physiological adaptation and optimization of kinship network.